How aware are our truck drivers regarding prevention of road traffic accidents? A cross-sectional study in Dankuni area, Hooghly - Das, Kuroram; Dasgupta, Aparajita; Naskar, N. N.; Pal, Bobby; Bandopadhyay, Lina (International Journal Of Community Medicine And Public Health, 2020)
Background: Road traffic accidents are an emerging global health problem. It is projected that road traffic injuries will move up to the third by the year 2020 among leading causes of the global disease burden. Methods: A cross-sectional study was conducted among 248 truck drivers in Dunkuni area Hooghly for a period of 2 years from August 2017 to July 2018. By simple random sampling 248 truck drivers were selected from 641 registered drivers of the two-truck driver’s association. Ethical clearance was obtained from the Institutional Ethics committee of AIIH and PH, Kolkata. After getting informed written consent for participation, the pre-designed pre-tested schedule was filled up. Data was analysed using SPSS16 version and bivariate analysis was done. For knowledge score (12 items), each item of positive response was scored as +2 and for negative response +1. Stress among truck drivers was assessed using perceived stress scale. Results: Mean age of the participants was 37 years. 24.2% participants studied up to secondary school and 134 (54%) belonged to class IV. 21.0% had history of alcohol addiction, 80.6% had high stress. Adequate knowledge of traffic sign was observed among 79.8% participants and overall adequate knowledge was found among 135 (54.4%) participants. Conclusions: Regular behavioural change communication sessions and intermittent sessions on safe-driving methods among truckers may prove beneficial in preventing road traffic accidents.